Expended Polystyrene (EPS) Waste as Sorbent for Crude Oil Spill Cleanup: From Laboratory Experiments to Field Application - Naser, Dr. Mohammed I. (Journal of Petroleum Research and Studies, 2017)
EPS is a major constituent of plastic waste. Reuse of waste EPS which is non-biodegradable, to useful products is a way of effective waste management. Oil is one of the most important energy sources but oil spill accidents often take place during the oil utilization process, resulting in threats to the environment. We reported the use of EPS waste to obtain an adsorbent material to cleanup crude oil spill from water. The effects of major factors such as sorption time, adsorbent surface areas, kind of surface (smooth or rough) and thermo-modification and mechanical modification (punching holes) were investigated on laboratory experiments and presented at ADIPEC 2014( Abu Dhabi International Petroleum Exhibition & Conference, 10-13 Nov., 2014, Session 52 Environment, SPE 172000-MS). The laboratory experiments carried out with about 0.9 g EPS sorbent for oil sorption times of 5 to 120 min at 350 g oil only and at 100 g oil over 500 mL water. The sorbent were punched with holes of 1.65 mm diameter. To verify the above laboratory experiments a field study for oil spill cleanup at crude oil pond from a rupture pipeline in Basrah was conducted. About 40 g EPS waste of small pieces (0.100-0.200 g) packed in 40x30 cm mesh net plastic bags. More than 40 bags were placed on the surface of a pond containing the spill crude oil over water. The pond was of about 6 meter diameter with oil layer of about 1.0 cm thickness. The bags were agitated manually after placing it on the oil surface to increase oil distribution to all EPS pieces. Oil sorption Capacity (OSC) of EPS in the field application increased with the increasing of the sorption times. The oil sorption was measured after 30 min sorption time and then every 15 min till 150 min. OSC of 43- 53 g oil/ g EPS sorbent for a sorption time of 30- 150 min respectively, were determined. The OSC are about 4 times the maximum OSC of the laboratory tests. The increasing in OSC of field application over laboratory tests due to utilization of all EPS 6 surfaces in place of one surface in laboratory tests, using lower density EPS and high density crude oil. The use of EPS waste in oil spill cleanup will reduce pollution in two ways, remediation of oil spill and reduce the landfill area due EPS waste